Evaluation of the Kura-Araxes migration: From a mono-factorial phantasm to a multi-dimensional phenomenon - Maziar, Sepideh (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Many scholars concerned with the Kura-Araxes cultural tradition take many aspects of this complex phenomenon for granted. In most publications, the expansion of this tradition across a vast area is treated like the movement of people from point A to B, or in the best case, as the waves of movement between these points. In most of them, migration is considered a direct reaction of people to population growth, lack of pasture lands, environmental stresses, and the Kura-Araxes as environmental or conflict refugees that flee a threat. These perspectives in recent years terminated to some skeptics regarding considering the distribution of the Kura-Araxes material culture as a result of migration. On the other hand, turning to be once again a buzzword, ‘migration’ as an explanation, is considered anachronistic among some archaeologists. This article will reevaluate different scenarios related to the Kura-Araxes phenomenon to see where we stand and how we can overcome these shortcomings. It seems that the Kura-Araxes phenomenon at the current state of our understanding suffers different drawbacks at different levels. The migration scenario itself and the mechanism behind it are still vague, and the relationship between the core area and diaspora is rarely addressed. It is suggested that approaches such as ‘resilience theory’ and discussing the Kura-Araxes phenomenon and migration in the context of social resilience will be more promising for the topic at hand.